2014
DOI: 10.1007/s13196-014-0128-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of charcoal from some promising bamboo species

Abstract: In this study, carbonisation of four bamboo species viz., Bambusa bambos, Dendrocalamus brandisii, D. stocksii and D. strictus was carried out. The effect of carbonisation temperature i.e., 300, 400, 500, 600, 700 and 800°C on yield and fuel properties (calorific value, ash, volatile content, fixed carbon content etc.,) of bamboo charcoal was investigated. The soaking time (1 h) and heating rate (5°C min -1 ) were kept constant for all experiments. A significant reduction in charcoal yield with increase in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…The low calorific value of original bamboo was attributed to the high water content and the effect of VMC. These results were similar to those reported by Hernandez-Mena et al (2014) and Kumar and Chandrashekar (2014) for the Bambusa and Dendrocalamus genus.…”
Section: Fuel Properties Of Original Bamboosupporting
confidence: 93%
“…The low calorific value of original bamboo was attributed to the high water content and the effect of VMC. These results were similar to those reported by Hernandez-Mena et al (2014) and Kumar and Chandrashekar (2014) for the Bambusa and Dendrocalamus genus.…”
Section: Fuel Properties Of Original Bamboosupporting
confidence: 93%
“…This result is similar to the findings of a few studies. Kumar and Chandrashekar (2014) observed the GCV of four bamboo species was between 25.1 and 28.7 MJ/kg carbonized at 700 and 800 0 C. The calorific value of Dendrocalamus giganteus (Sembilang bamboo) and Phyllostachys edulis (Moso bamboo) reported by Park et al (2020) carbonized at 800 o C was 28.3 and 31.9 MJ/kg, respectively.…”
Section: Gross Caloric Valuementioning
confidence: 88%
“…The highest mean ash content recorded in charcoal made from B. vulgaris was in the bottom section. High ash content in bamboo is attributed to high silica content (Kumar and Chandrashekar 2014). The ash content percentage is important for selecting a biomass fuel (Ruiz-Aquino 2019).…”
Section: Ash Contentmentioning
confidence: 99%
“…Rousset et al (2011) showed that the fixed carbon content of Bambusa vulgaris torrefied at 220, 250, and 280 °C increased with increasing temperature, whereas the VMC decreased as temperature increased. According to Kumar and Chandrashekar (2014), the higher FCC value in charcoal prepared at higher temperatures may be caused by VMC removal from the wood during the pyrolytic process. Kwon et al (2012) reported that the fixed carbon content of cork oak carbonized at 400 to 1,200 °C increased as the carbonization temperature increased.…”
Section: Fixed Carbon Contentmentioning
confidence: 99%